Assessing the potential of alternative energy from mangrove species in Segara Anakan, Central Java, Indonesia - ENDANG HILMI; FITRI WINTARTI; MUKHTAR EFFENDI; MOH HUSEIN SASTRANEGARA; RAHAB RAHAB; NORMAN ARIE PRAYOGO; TEUKU JUNAIDI; HENDRAYANA HENDRAYANA; TRI NUR CAHYO; ROSE DEWI (Society for Indonesian Biodiversity, 2025)
Abstract. Hilmi E, Wintarti F, Effendi M, Sastranegara MH, Rahab, Prayogo NA, Junaidi T, Hendrayana, Cahyo TN, Dewi R. 2025. Assessing the potential of alternative energy from mangrove species in Segara Anakan, Central Java, Indonesia. Biodiversitas 26: 2832-2842. Mangroves have the potential to be developed for alternative energy to support the utilization of non-renewable energy because mangrove species have high carbon content, high caloric value, and high bulk density. This research aimed to analyze the potential of mangrove species as alternative energy resource to reduce non-renewable energy using the analysis of carbon percentage, caloric value, and fuel fumes. This research used destructive approach and laboratory analysis to analyze energy properties of mangrove species in Segara Anakan, Cilacap District, Central Java, Indonesia. The energy properties included percentage of fixed carbon (%), percentage of charcoal (%), wood density (gr/cm3), fuel fumes (ppm), total Sulphur (%), caloric energy value (cal/gr) and class of energy using SNI (Indonesian National Standards) and American Society for Testing and Materials (ASTM) systems. This study also analyzed relationship between carbon percentage and energy properties. Mangroves in Segara Anakan contained biomass between 341.90-493.93 ton/ha with carbon percentage between 50.8-63.2% (average 59.1%), fuel fumes between 512.3-640.0 ppm (average 589.0 ppm) and caloric energy value between 6235-7230 cal/gr (average 6796.3 cal/gr). Lanscape scale analysis revealed that Rhizophora apiculata, Rhizophora mucronata, Bruguiera gymnorrhiza, and Ceriops tagal had the highest potential to produce alternative energy as a substitute for non-renewable energy. These species are recommended for mangrove rehabilitation and reforestation if aiming to generate renewable energy resource.